(untitled) (Politeja, 2016)
Debate on the new strategy of external security at the forum of European Union institutions and bodies in 2012-2015 The subject of the article is the debate on the new external security strategy, which has been ongoing in the European Union since 2012. It presents the position of the European Council and the Council for Foreign Affairs, the European Commission, the European Parliament as well as the Interparliamentary Conference for a Common Foreign and Security Policy and Common Security and Defence Policy. In so far as these first two institutions play a decisive role in shaping a common security and defence policy, the influence of the next two is still limited, in spite of the fact that it has increased since the coming into force of the Lisbon Treaty of 13 December 2007. In turn, the Interparliamentary Conference, whose members include representatives of the European Parliament and national parliaments, functions only as an advisory body in this area.